Host range, damage and seasonality of fruit flies in Sennar State, Sudan - Gesmallah, Abdelaziz E.; H.H. Bashir, Nabil; E. Elkashif, Mohamed; O.H. Assad, Yousif (Gezira Journal of Agricultural Science; Vol 10 No 1 (2012), 2023)
Fruit flies (Diptera: Tephritidae) are one of the most economically important groups of insects in the afrotropical region because they cause damage to fruits and vegetables. Integrated fruit fly (FF) control program requires accurate data about taxonomy, incidence, distribution and seasonality of the members of this pest. Surveys and collection missions were carried out in Sennar State during January  2006- January 2008. Yellow sticky traps were used for adult collection. Trapped  fruit flies were labeled, identified and counted monthly to estimate their abundance throughout the year. In addition, infested fruits of mango, guava, grapefruit, orange, banana, melons, pumpkin, watermelon, and the wild magad (Cucurbitaceae) were collected monthly from the surveyed areas. Larvae were reared till the adult stage and identified. Field infestation rate of FF species was determined on mango and guava at Singa area. Percentage of FF infestation on mango Baladi cultivar was 10% in March, 15% in April and 20% in May. During the period from June to August, Abu Samaka cultivar was the only mango cultivar available, and accordingly, was subjected to a heavy attack by the FF. The infestation reached 30% in June and 50% in July. The FF moved to guava, during the period from October to December. The rate of FF infestation on guava was very high during this period and ranged from 80% to 90%. Mango fruits in Singa area were infested by Bactrocera invaden s (Drew, Tsuruta and White) (80%), C. cosyra (19.8%) and Dacus longistylus (Wiedemann) (0.2%) of the total emerged adults. This was the first record for the latter species in a host other than Calotropis procera (Apocynaceae). Guava fruits were infested by B. invadens (84.5%), C. cosyra (15.3%), and C. quinaria (Bezzi) (0.2%) of the total emerged adults. B. invadens seemed to out-compete and replace the indigenous species. Cucurbit fruits hosted D. ciliatus (Leow) only. The wild magad fruits hosted B. invadens and B. cucurbitae   (Coquillet). The highest population of B.invadenss was observed during July and  December (254 and 253 adults/trap, respectively). March and April showed the lowest population due to higher temperatures and low relative humidity.